Worldwide and Brazilian scientific publications on Leishmaniasis in the first 19 years of 21st century: a bibliometric study - Saulo Nascimento de Melo; Amanda Cristina Silva; David Soeiro Barbosa; Heber Paulino Pena; Shaytner Campos Duarte; Rafael Gonçalves Teixeira-Neto; Eduardo Sergio da Silva; Vinícius Silva Belo (Journal of Infection in Developing Countries)
Introduction: Leishmaniasis is a set of tropical diseases widely distributed throughout the world. Publications concerning different aspects of leishmaniasis have shown an increasing trend in recent years, especially in Brazil, where this disease has been under continuous expansion. The present study analyzes the data and assess trends in publications on leishmaniasis in Brazil and worldwide.